2019
DOI: 10.1016/j.proci.2018.05.128
|View full text |Cite
|
Sign up to set email alerts
|

Heat release analysis for rapid compression machines: Challenges and opportunities

Abstract: Heat release analysis (HRA) is commonly used in combustion studies to derive understandings of chemical and physical processes in situations where direct measurement is not practical. In internal combustion engines, it is typically based on crank-angle resolved pressure diagnostics. However, it has not been applied extensively to rapid compression machine datasets. There are various challenges associated with rigorous application of HRA, including a reasonable accounting of physical processes that occur during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…Figures 5 and 6 show the experimental and simulated HRRs prior to the main ignition event plotted against the aHR and time from the maximum pressure gradient, respectively, at temperatures of 710, 770, and 830 K. LTHR is common in degenerately branched systems and describes exothermic events that occur before the main stage of heat release, which describes the autoignition event 79 . LTHR is indicated by a relatively sharp peak in HRR and an associated rise in pressure, which also produces a visible CH 2 O* chemiluminescence and is considered to be chemically due to the decomposition of ketohydroperoxides to produce multiple OH radicals 54 . In some cases, LTHR may be followed by an intermediate stage of heat release (ITHR), which also occurs before the autoignition event.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Figures 5 and 6 show the experimental and simulated HRRs prior to the main ignition event plotted against the aHR and time from the maximum pressure gradient, respectively, at temperatures of 710, 770, and 830 K. LTHR is common in degenerately branched systems and describes exothermic events that occur before the main stage of heat release, which describes the autoignition event 79 . LTHR is indicated by a relatively sharp peak in HRR and an associated rise in pressure, which also produces a visible CH 2 O* chemiluminescence and is considered to be chemically due to the decomposition of ketohydroperoxides to produce multiple OH radicals 54 . In some cases, LTHR may be followed by an intermediate stage of heat release (ITHR), which also occurs before the autoignition event.…”
Section: Resultsmentioning
confidence: 99%
“…Goldsborough et al 54 . have shown in previous work that HRA can be applied effectively to RCM experiments, facilitating the investigation of low‐temperature heat release behavior for a wide range of thermodynamic conditions.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The validation criterion of the model predictions against experiments is pre-flame stage timing τ I . Goldsborough [5] has shown that this stage is over when the magnitude of current pressure exceeds the initial by one more than 5 %.…”
Section: A Kinetic Mechanismmentioning
confidence: 99%